Comparative Efficiency of APRI vs. FIB-4 in Detecting Advanced Liver Fibrosis in NAFLD and NASH - Noureen, Sadaf; Fatima, Hareem; Butt, Amina Hasan; Zia, Abeeha; Abid, Muhammad Huzaifa; Malik, Iqra (Biological and Clinical Sciences Research Journal, 2025)
Non-alcoholic fatty liver disease (NAFLD) and non-alcoholic steatohepatitis (NASH) are significant causes of chronic liver disease, with the progression to advanced fibrosis (F3–F4) significantly impacting prognosis. Objective: To compare the diagnostic accuracy of APRI and FIB-4 scores in detecting advanced liver fibrosis (F3–F4) in NAFLD and NASH patients, using transient elastography (FibroScan) as the reference standard. Methods: This cross-sectional, observational study was conducted at Fauji Foundation Hospital from March 2024 to March 2025. A total of 120 adult patients aged between 18 and 70 years with a confirmed diagnosis of NAFLD or NASH were included in the study. All data were collected using a standardized form. Variables recorded included patient demographics (age, sex, body mass index), comorbidities such as diabetes and hypertension, and relevant laboratory values, specifically serum AST, ALT, and platelet counts. Results: Out of 120 patients, 42 (35%) had advanced fibrosis on fibroscan. The FIB-4 score showed superior diagnostic performance with an AUROC of 0.86 (95% CI: 0.79–0.91), sensitivity of 78.5%, specificity of 85.9%, PPV of 75.6%, and NPV of 87.5%. APRI showed an AUROC of 0.79 (95% CI: 0.71–0.86), sensitivity of 71.4%, specificity of 80.8%, PPV of 66.7%, and NPV of 84.4%. Subgroup analysis confirmed the consistent superiority of FIB-4 across age and diabetic status. FIB-4 also had a lower misclassification rate (15.8%) compared to APRI (21.7%). Conclusion: It is concluded that while both APRI and FIB-4 are practical non-invasive tools for assessing liver fibrosis in NAFLD/NASH, FIB-4 is more accurate in detecting advanced fibrosis. Its greater diagnostic power and stability across subgroups support its use as the preferred first-line fibrosis assessment tool in routine clinical practice.